Tác phẩm được tặng Giải thưởng Hồ Chí Minh : Nghiên cứu văn học Việt Nam và văn học thế giới 1945 - 1984 - Đặng, Thai Mai (Tác phẩm được tặng Giải thưởng Hồ Chí Minh., 2003)
Nghiên cứu văn học Việt Nam và văn học thế giới 1945 - 1984.